City of lost souls - Clare, Cassandra (London : Walker Books, 2012)
When Jace vanishes with Sebastian, Clary and the Shadowhunters struggle to piece together their shattered world and Clary infiltrates the group planning the world's destruction.
Young Adult.
Young Adult
Keywords: Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Supernatural -- Juvenile fiction; Vampires -- Juvenile fiction; Demonology -- Fiction; Fantasy; Magic -- Fiction; Supernatural -- Fiction; Vampires -- Fiction; Demonology -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Vampires -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Fantastic fiction; Fantastic fiction